Gender capacitation of extension and rural advisory services in West and Central Africa: the learning journey and outcomes - Maiga, Mariame; Gebremedhin, Bethel; Kpadonou, G Esaie; Ganyo, Komla Kyky; Dieng, Fatou; Segnon, Alcade Christel; Lamien, Nieyidouba; Zougmore, Robert Bellarmin (2025)
This InfoNote documents a regional training workshop, organized in collaboration with FAO, to capacitate stakeholders working in extension services in FSRP countries, on gender mainstreaming in extension advisory programmes. Agricultural Extension and Advisory Service plays a critical role in access, adoption, and scaling of technologies and Innovations, to enhance food productivity to feed the populations. Gender Responsive Agricultural Extension and Advisory Services can be achieved through capacitation thereby contributing to respond to the increasing youth unemployment across Africa, with participation of underprivileged as women and youth in agricultural commercialization and industrialization for empowerment. Gender capacitation of extension institutions is key for designing and delivering gender responsive extension advisory services to enable rural women and youth to effectively benefit. In collaboration with FAO, AICCRA-FSRP, CORAF capacitated Extension Officers from West and Central Africa, on gender mainstreaming in Agricultural Extension and Advisory Services to foster gender responsive AEAS, needed for the transformation of agriculture in the region. Main modules covered are (i) basic concepts in gender and agricultural extension services, (ii) methods and tools for conducting gender analysis in extension planning and (iii) approaches for mainstreaming gender in Agricultural Extension and Advisory Services. 23 participants (with 61% women) from Benin, Chad, Côte d'Ivoire, Mali, Niger, Nigeria, Senegal and Togo who are directors or department heads of agricultural advisory and extension services from were capacitated and went back home with the promise to extend this knowledge to their pairs. Future actions are oriented to the follow-up on the activities in these countries to ensure the application of the acquired skills for transforming the agri-food systems in West and Central Africa.